The Relationship Between Occupational Demands and Well-Being of Performing Artists: A Systematic Review - Willis, Simone; Neil, Rich; Mellick, Mikel Charles; Wasley, David (Frontiers in Psychology, 2019)
Abstract: Background: Performing artists are exposed to a range of occupational demands from organisational, interpersonal and intrapersonal sources, which may impact their well-being. The aim of this systematic review was to evaluate and synthesise the literature where researchers have considered the relationship between occupational demands and well-being in performing artists. Methods: A mixed-methods systematic review was conducted including professional and student performing artists. Quantitative, qualitative and mixed-methods study designs were eligible for inclusion in the review. A total of 14 databases were searched from their inception through to October 2017, including MEDLINE, EMBASE and Scopus. Critical appraisal was conducted using the Mixed-Methods Appraisal Tool and results presented as a narrative synthesis. Results: A total of 20 studies were included in the review, comprising of quantitative (n=7), qualitative (n=9) and mixed-methods (n=4) study designs. Several frameworks of occupational stress and well-being were explored in relation to the results. Organisational, social and emotional demands were associated with lower well-being. Conversely, music-making, performance activities and social support were reported to be resources and were related to higher well-being. Conclusion: This systematic review highlights the need for researchers in this field to adopt methodologically robust study designs, which are informed by appropriate theoretical frameworks. The paucity of high quality and theoretically informed research in this area is a hindrance to the development of evidence-based interventions for this population.